A Field Observation on Lightning Performance Improvement of Overhead Distribution Lines - Zoro, Reynaldo; Mefiardhi, Ryan; Hidayat, Syarif; Mardiana, Redy (Journal of Engineering and Technological Sciences, 2009)
Two feeders of 20 kV overhead distribution lines which are located in a high lightning density area are chosen to be observed as a field study due to their  good  lightning  performance  after  improvement  of  lightning  protection system.  These  two  feeders  used  the  new  overhead  ground  wire  and  new  line arrester  equipped  with  lightning  counter  on  the  main  lines.  The  significant reduced  of  lines  outages  are  reported.  Study  was  carried  out  to  observe  these improvements  by  comparing  to  the  other  two  feeders  line  which  are  not improved and not equipped yet with the ground wire and line arrester. These two feeders  located  in  the  nearby  area.  Two  cameras  were  installed  to  record  the trajectory of the lightning strikes  on the improved lines. Lightning peak currents are  measured  using  magnetic  tape  measurement  system  installed  on  the grounding  lead  of  lightning  arrester.  Lightning  overvoltage  calculations  are carried out by using several scenarios based on observation results and historical lightning data derived from lightning detection network. Lightning overvoltages caused by indirect or direct strikes are analyzed to get the lightning performance of  the  lines.  The  best  scenario  was  chosen  and  performance  of  the  lines  were improved significantly by installing overhead ground wire and improvement of lightning arrester installation.